A CONSTRUÇÃO DISCURSIVA DO MÁRTIR Um olhar a partir da Passio Sanctorum Perpetuae et Felicitatis - Matos, Denilson da Silva (2016)
The purpose of this research is to analyze the Passio Sanctorum Perpetuae et Felicitatis, highlighting how this martyrdom report presents its main characters, that is, as the martyrs are built narratively. The research works martyrdom in early Christianity as a discursive phenomenon, that is, as a practice that emerges from a discursive interaction between the main cultures in constant dialogue in the early centuries of the Christian era, Greco-Roman, Jewish and Christian. For this analysis, we will dialogue with the works of Judith Perkins and Candida Moss, Christine Trevett, William Tabbernee, Rex D. Butler, among others, as well as we will use the dialogic concept of Mikhail Bakhtin. The research also discusses the latest research about the martyrdom theme. By examining this ideology developed in early Christianity could identify the discursive construction of a character linked to the practice martyrdom, the martyr. We present the various characteristics attributed to the martyr in a corpus of early Christian texts known as Acts of the martyrs, highlighting the high status achieved by these men and women who faced death. The martyr, to face and experience death receives invaluable powers, which makes it a special person, an ideal Christian who is above the ecclesiastical hierarchy and even the heavenly hierarchy. The Passio Sanctorum perpetuae et Felicitatis is an example of early Christian literature that shares these ideas that pervade the early centuries of the Christian era. By analyzing the plot of the narrative composition of martyrdom report identified traces of the discourse on martyrdom and the martyr present in early Christianity.